The Role of Multilateral Development Banks in Humanitarian Action and Sustainable Development (Glocalism: Journal of Culture, Politics and Innovation, 2022)
Of all international organisations, Multilateral Development Banks (MDB) are not the most well-known nor the most scrutinised neither by the academy nor the public. However, they play a major role as financial institutions for the purpose of development. The article, drawing on the broader field of Humanitarian Aid and Aid for Development discusses the role of those agencies, particularly with reference to the connections between the humanitarian and the development dimensions, and within this later case, assessing their efforts in order to tackle poverty and to abide by sustainability concerns. The conclusion highlights some of the main findings, mainly with reference to two cases, the European Development Bank (EIB) and the New Development Bank (NDB).
Keywords: development aid; humanitarian aid; multilateral development banks; sustainability; poverty